VARIABEL ANTESENDEN YANG MEMPENGARUHI PROFITABILITAS DI BURSA EFEK INDONESIA - Samidah, Neneng; Risal, Risal; Kristiawati, Endang; Wulandari, Renny (JURNAL BISNIS & AKUNTANSI UNSURYA, 2025)
Profitability is one of the parameters of a company's success. In line with the national economic recovery in 2022, it will provide a significant increase in company profitability. However, in reality, companies still experience a decline in the level of profitability which is reflected in company profits. This research aims to determine the influence of company size, liquidity, leverage, efficiency and working capital turnover on profitability in Infrastructure, Utility and Transportation sector companies listed on the Indonesia Stock Exchange in 2019-2022. The population in this research is companies listed on the Indonesia Stock Exchange in the Infrastructure, Utilities and Transportation sectors. The research sample was 13 infrastructure, utility and transportation companies obtained using the method purposive sampling. Data collection techniques use documentation. Data processing and analysis techniques were carried out using multiple linear regression analysis techniques. The research results show that partially liquidity, efficiency, and working capital turnover do not have a significant positive effect on company profitability. Where as Firm size has a significant positive effect Firm size has a significant positive effect while leverege negative and significant effect on profitability in Infrastructure, Utilities and Transportation sector companies listed on the Indonesia Stock Exchange in 2019-2022.Keywords:Â Â Profitability, Firm Size, Liquidity, Leverage, Efficiency.